Differential amniotic fluid cytokine profile in women with chorioamnionitis with and without funisitis. (2nd July 2016) - Revello, Rocio; Alcaide, Maria Jose; Dudzik, Danuta; Abehsera, Daniel; Bartha, Jose L.
Abstract: Objectives : To evaluate whether the amniotic fluid (AF) cytokine profile in women with chorioamnionitis may differentiate between those with and without funisitis. Subjects and methods : Forty women at high risk of chorioamnionitis were studied. Gestational age at study was 26.94. Amniocentesis, universal and specific polymerase chain reaction, and microbiological cultures were performed. AF IL-1β, IL-2, IL-4, IL-6, IL 8, IL-10, IL-12, TNF-alpha, IFN-gamma, and MMP-8 were measured by multiplex assay. After delivery, the placenta and umbilical cord were studied histologically. Comparisons were made between three groups: controls, and chorioamnionitis with and without funisitis. Results : In 25 cases, the histological findings were normal (61.5%). The remaining 15 composed of 9 cases of chorioamnionitis alone (9/40; 23.1%) and 6 cases of chorioamnionitis plus funisitis (6/40; 15.4%). All AF cytokine levels were significantly higher in the cases with chorioamnionitis in comparison to controls, except for IFN-gamma. The comparisons between the three groups showed significant differences between chorioamnionitis alone and chorioamnionitis plus funisitis in IL-1β, IL-6, IL-10, IL-12, IL-8, and TNF-alpha, with the levels being higher when funisitis was present. Logistic regression found a powerful predictive model for funisitis including the following cytokinesIL-4, IL-10, IL-12, and IL-8. Conclusions : Measurements of AF interleukins 4, 10, 12, and 8 allow to identify cases with funisitisin women at high risk of chorioamnionitis.